Wnt4 participates in the formation of vertebrate neuromuscular junction. - Laure Strochlic (Public Library of Science (PLoS), 2012)
Neuromuscular junction (NMJ) formation requires the highly coordinated communication of several reciprocal signaling processes between motoneurons and their muscle targets. Identification of the early, spatially restricted cues in target recognition at the NMJ is still poorly documented, especially in mammals. Wnt signaling is one of the key pathways regulating synaptic connectivity. Here, we report that Wnt4 contributes to the formation of vertebrate NMJ in vivo. Results from a microarray screen and quantitative RT-PCR demonstrate that Wnt4 expression is regulated during muscle cell differentiation in vitro and muscle development in vivo, being highly expressed when the first synaptic contacts are formed and subsequently downregulated. Analysis of the mouse Wnt4⁻/⁻ NMJ phenotype reveals profound innervation defects including motor axons overgrowing and bypassing AChR aggregates with 30% of AChR clusters being unapposed by nerve terminals. In addition, loss of Wnt4 function results in a 35% decrease of the number of prepatterned AChR clusters while Wnt4 overexpression in cultured myotubes increases the number of AChR clusters demonstrating that Wnt4 directly affects postsynaptic differentiation. In contrast, muscle structure and the localization of several synaptic proteins including acetylcholinesterase, MuSK and rapsyn are not perturbed in the Wnt4 mutant. Finally, we identify MuSK as a Wnt4 receptor. Wnt4 not only interacts with MuSK ectodomain but also mediates MuSK activation. Taken together our data reveal a new role for Wnt4 in mammalian NMJ formation that could be mediated by MuSK, a key receptor in synaptogenesis.